Strictly non-volterra Quadratic Stochastic Operator (QSO) on 3-dimensional simplex - Ganikhodjaev, Nasir; Jusoo, Siti Hasana (Institute of Physics Publishing, 2018)
In this paper, we investigate the dynamics of the Lebesque quadratic stochastic operator on the set of all Lebesque measures of the set X = [0,1] . We consider the family of functions such that for any fixed x, y a probability measure P(x, y,.) is absolutely continuous with respect to usual Lebesque measure on X with simple Radon-Nikodym derivative. We construct the family of strictly non-Volterra quadratic stochastic and show that their dynamic behavior coincides with dynamic of strictly non-Volterra quadratic stochastic operator on 3-dimensional simplex.